Commerce or Conflict? – A Reinterpretation of Two Late 16th-Century Shipwrecks from the Gulf of Finland - Tevali, Riikka (The international journal of nautical archaeology, 2025)
Several decades ago, two shipwrecks were discovered in the archipelago of the Gulf of Finland. During excavations they were found to have identical galley structures and similar find assemblages. Based on this, the wrecks were dated to the end of the 16th century AD and interpreted as Dutch trade ships. This article looks through the available archaeological evidence and argues that previous interpretation of the wrecks does not take into consideration the entire archaeological evidence available from both sites. By studying the social and historical contexts of the wrecks, it is possible to find other explanations as well, which might fit better with the contemporary political realities, namely that the ships could have belonged to the Swedish nobility.